Assessment of liquid media requirements for storing and evaluating respiratory cilia motility - Francis,Richard (PeerJ, 2025)
Mucociliary clearance is critical for maintaining normal lung function. Respiratory cilia which drive mucociliary clearance are commonly studied by measuring cilia beat frequency (CBF). There is currently significant variation within the literature regarding what is a normal value for CBF, this may be due in part to the large variety of liquid media used to suspend, maintain, and image ciliated cells. This study aimed to conduct a thorough examination to assess how media choice influences respiratory cilia motility. To accomplish this, Adult C57/BL6 mouse trachea samples were incubated in eight commonly used liquid media including: Saline, Dulbecco’s Phosphate-Buffered Saline (DPBS), Hanks’ Balanced Salt Solution (HBSS), Medium 199 (M199), Dulbecco’s Modified Eagle’s Medium (DMEM), Roswell Park Memorial Institute Medium (RPMI), Minimum Essential Medium (MEM), and Leibovitz’s L-15 Medium (L-15); with or without 10% FBS supplementation. The effects of storage time (0–12 hours) and storage temperature (4 °C or room temperature) were also assessed. All media except saline were found to be equally effective in maintaining cilia function in airway samples that were freshly harvested and immediately imaged. Saline, however, significantly reduced the number of cells with motile cilia. A more complex pattern emerged when samples were stored before imaging. In saline, cilia function was significantly impaired after just one hour of storage. Samples stored in all other media showed strong maintenance of motile cilia function, with only minor changes. Notably, cilia function was better preserved with storage at 4 °C, while room temperature storage generally led to significant increases in CBF, especially in media containing FBS. Lastly, FBS supplementation was essential for maintaining cilia motility in L-15 media, as L-15 without FBS resulted in significant decreases in cilia motility following storage at either 4 °C or room temperature. In conclusion, saline should only be used if cilia are to be imaged immediately, as cilia stored in saline quickly lose motile function. All other commonly used media appear equally capable of maintaining motile cilia function for up to 12 hours when stored at 4 °C. Surprisingly, DPBS was just as effective as more expensive media in preserving ciliated samples. Storing ciliated tissue at room temperature generally leads to increased CBF, particularly in media containing FBS. Finally, L-15 media alone specifically requires the addition of 10% FBS to maintain cilia motility. These findings provide a valuable foundation for standardizing the handling, collection, and transport of ciliated samples for motile cilia assessment.
Keywords: Respiratory epithelium; Cilia beat frequency; Cilia generated flow